Tiếp cận hệ thống trong điều khiển các quá trình công nghệ - Châu, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
A broad class of technology processes for production of social consumption products in material and energy form is studied by system engineering. The last product is used as existence condition of the mentioned above class. The system of axiom and principal definitions, theorems for structure, analysis and synthesis, observation and control to this class of technology processes is createt.